Social Skills Practice Strategy Opportunities for Students With EBD. (August 2021) - Kumm, Skip; Reeder, Jacob; Farrell, Erin
Students with emotional and behavioral disorders (EBD) are likely to require interventions to help them navigate the social demands of the school environment. Several meta-analyses of social skills interventions have been conducted, which have provided guidance and demonstrated the effectiveness of social skills training for students with EBD. This article details a framework for teaching and practicing social skills interventions. Included in it are descriptions of several social skills strategies and ways in which the teaching of them can be individualized to meet the needs of students with EBD.